2016
DOI: 10.1093/ehjci/jew054
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological validation of optical frequency domain imaging to quantify various types of coronary calcifications

Abstract: AimsThis study evaluated whether optical frequency domain imaging (OFDI) could identify various coronary calcifications and accurately measure calcification thickness in comparison with histopathology. Methods and resultsA total of 902 pathological cross-sections from 44 coronary artery specimens of human cadavers were examined to compare OFDI and histological images. Histological coronary calcification was classified into four different types: (i) superficial dense calcified plates, (ii) deep intimal calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…(5) OCT is prone to inherent limitations including the inability to analyze micro-calcifications as well as a limited penetration depth, which makes identification of the deep trailing edge of calcium and subsequent area measurements of deep deposits difficult. 42,43 Due to this limited penetration depth, it is not possible to image medial calcification in the coronary vessels outside of exceptional cases. Instead, in severely diseased atherosclerotic coronary vessels, it is the atherosclerotic plaque within the medial border which is imaged, and which has eliminated a true intimal layer.…”
Section: Limitationsmentioning
confidence: 99%
“…(5) OCT is prone to inherent limitations including the inability to analyze micro-calcifications as well as a limited penetration depth, which makes identification of the deep trailing edge of calcium and subsequent area measurements of deep deposits difficult. 42,43 Due to this limited penetration depth, it is not possible to image medial calcification in the coronary vessels outside of exceptional cases. Instead, in severely diseased atherosclerotic coronary vessels, it is the atherosclerotic plaque within the medial border which is imaged, and which has eliminated a true intimal layer.…”
Section: Limitationsmentioning
confidence: 99%
“…We previously reported that heterogeneous type I tissue showed fibroatheroma formation within the neointima, and Type IV presented with tissue calcium accumulation within the neointima on histology. 9,10,20 The development process of atherosclerotic lesion within neointima, known as neoatherosclerosis, may be gradual compared with that in the native coronary artery. This finding is also supported by previous studies, which reported that the development of atherosclerosis is a gradual and complex process caused by the interaction of various risk factors, endothelial cell dysfunction, and lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the aorta, there was a solitary lesion of nodular calcifica- Surprisingly, these calcified nodules were benign, meaning they were unlikely to cause coronary events during a three-year follow-up study. More recently, Hao et al 4) and Saita et al 5) also reported uncomplicated calcified nodules, which are not associated with thrombosis. The present case provides further evidence to support their observations in the coronary artery.…”
mentioning
confidence: 96%